Long-term operational performance following spin-offs: Evidence from the medical technology industry - Cehic, Haris; Mellbring, Linus (My University, 2023)
Spin-offs function as a strategic tool for firms aiming to adjust their portfolios in response to strategic changes and evolving business environments. From an op- erational perspective, a common motivation for spin-offs is tied to expectations of performance improvements where the mechanisms behind this stem from abilities to increase focus on core businesses as the parent and the spun-out entity can achieve greater organizational freedom, ability to change strategy, and focus the strategy more narrowly. There has been a high activity of spin-offs in the medical tech- nology industry and an underpinning reason for this is that firms aim to mitigate industry-wide challenges through spin-offs with the motivation of achieving increased operational focus to capture long-term growth opportunities. Hence, the purpose of this study was to analyze spin-offs in the medical technology industry. To fulfill this purpose, a mixed-method approach was employed to investigate the operational performance of spin-offs in the medical technology industry through a combination of quantitative and qualitative analyses. The findings indicate that post-spin-off im- provements in operating performance, as measured by ROA, are mainly associated with the parent firms rather than the spun-off entities. In the studied sample, the parents benefited from increased focus as it facilitated strategy execution, capital allocation, and access to capital. In addition, evidence suggests that the parent firms spun out underperforming firms and that the spun-out entities prioritized growth over profitability to a greater extent.
Keywords: Spin-off; Operational performance; Long-term performance; Medical- technology industry; Return on assets; Divestiture; Corporate restructuring